Tourist harassment and its impact on tourism experience - Zafer ÖTER; Mehmet Yavuz ÇETINKAYA (Tourism and Hospitality Management)
Purpose – This study addressed the harassment of international tourists visiting Istanbul, debated both in print and visual media as a global problem for tourist destinations, and investigated its potential impact on the tourism experience. Methodology/Design/Approach – This study utilized a questionnaire, which was first outlined by De Albuquerque & McElroy (2001) and later developed by Kozak (2007) in English. A total of 500 international tourists from 40 different nationalities residing in 45 different countries located in 11 different regions were surveyed in 8 main languages at Sabiha Gokcen International Airport. Findings – The findings revealed that international tourists were subjected to six types of tourist harassment: persistence of vendors, begging, verbal abuse, sexual harassment, physical abuse, and peddling of drugs. Finally, the study revealed that harassment had a negative impact on the overall tourism experience, including variables like satisfaction level and future behavioral intentions. Originality of the research – This study added to a still-maturing stream of research on tourist harassment by coming up with empirical evidence from one important tourist destination, Istanbul, Türkiye and providing several important theoretical and practical implications